Reactive hyperplasic lesions of the oral cavity: A survey of 295 cases at a Tertiary Health Institution in Kerala - Vidyanath, S (J Oral Maxillofac Pathol, 2015)
BACKGROUND: The aim of this study was to review the clinicopathologic features of reactive hyperplastic lesions (RHLs) of the oral cavity at a Tertiary Health Institution in Kerala and compare these data with those of previously reported studies. MATERIALS AND METHODS: The patient case files from the Department of Oral and Maxillofacial Pathology during the period between January 2007 and December 2011 were reviewed for cases of RHLs of the oral cavity. Both clinical and histopathological diagnoses of reactive lesions were selected for the study. Data including the type of the lesion, age, gender and the site involved were collected. RESULTS: From a total of 2753 cases reviewed, 295 histologically diagnosed cases of RHLs were obtained with a prevalence of 10.7%. The data consist of 85 (28.8%) males and 210 (71.2%) females. The most common lesion clinically was traumatic fibroma (69.3%) and histologically fibrous hyperplasia (51.9%). The reactive lesions clinically presented as either sessile (54.9%) or pedunculated (45.1%) lesions. CONCLUSION: The clinical features of reactive hyperplasia among our patients were similar to those reported previously with divergence in some analyzed data. The novelty in our study was the correlation between histopathology and clinical features which were not reported in literature until date.